PENDIDIKAN MULTIKULTURAL DI PESANTREN: MEMBANGUN KARAKTER INKLUSIF DI TENGAH KEBERAGAMAN BUDAYA - Muhammad Fadli Al Farizi; Adi Prasetyo (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
Islamic boarding schools (pesantren) are currently challenged by the increasing cultural diversity among students, which may create social gaps if not managed effectively. This condition requires an educational approach that promotes respect for differences within the framework of Islamic values. This study employs a qualitative library research method to examine the implementation of multicultural education in strengthening inclusive character among students in traditional pesantren in Indonesia. Data were collected through systematic analysis of relevant literature, including scholarly books, journal articles, and official documents related to pesantren educational models and multiculturalism. The findings reveal that values such as tolerance, cooperation, and respect for cultural identity can be internalized through pesantren cultural practices that emphasize collective decision-making, shared dormitory life, and appreciation of students’ diverse regional backgrounds. The study concludes that multicultural education rooted in pesantren culture contributes significantly to the development of inclusive character by promoting Islamic values of rahmatan lil ‘alamin. The implications highlight the importance of developing multicultural education models that are adaptive to the dynamics of pluralism in Islamic education in Indonesia.